2016
DOI: 10.1177/1540796915626009
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Beliefs About the Participation of Students With Severe Disabilities in School Clubs

Abstract: The purpose of this study was to investigate teachers' beliefs about the participation of students with severe disabilities (SD) in school clubs. Participants were special education teachers (N = 60) of middle and junior high school students with SD from one state. Data were collected using a survey. Results indicate that teachers value including students in school clubs and believe that students benefit from engaging in club activities, yet they did not view this setting as a place to address curricula. Issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…In a recent study we conducted (see Pence & Dymond, 2015), we found that special education teachers who had experience including students with severe disabilities in school clubs believed that students benefited from increased learning; however, these teachers rated student learning notably lower than other benefits (e.g., student looked forward to attending the school club, student experienced an increased sense of belonging within the school community). In addition, teachers believed that their students benefited substantially more from learning functional skills (i.e., communication, choice making, independent living skills) during school clubs than skills linked to grade-level academic standards.…”
Section: Benefits Of Participation In Extracurricular Activitiesmentioning
confidence: 91%
See 2 more Smart Citations
“…In a recent study we conducted (see Pence & Dymond, 2015), we found that special education teachers who had experience including students with severe disabilities in school clubs believed that students benefited from increased learning; however, these teachers rated student learning notably lower than other benefits (e.g., student looked forward to attending the school club, student experienced an increased sense of belonging within the school community). In addition, teachers believed that their students benefited substantially more from learning functional skills (i.e., communication, choice making, independent living skills) during school clubs than skills linked to grade-level academic standards.…”
Section: Benefits Of Participation In Extracurricular Activitiesmentioning
confidence: 91%
“…Among these activities, Kleinert et al (2007) found that school clubs were the most frequent type of organized activity in which students participated. Several research studies have also found that students with severe disabilities are typically supported by one or more individuals during extracurricular activities, including special education teachers, paraeducators, general education teachers, peers, and parents (Eriksson, 580029T CXXXX10.1177 Kleinert et al, 2007Pence & Dymond, 2015.…”
Section: § 614[d][1][a][i])mentioning
confidence: 97%
See 1 more Smart Citation
“…Research investigating the perceptions of school personnel suggests several barriers that limit the participation of students with disabilities. These barriers include student characteristics (e.g., cognitive, communication, social, behavioral), insufficient extracurricular activity options and supports, lack of parent and teacher support, transportation issues, and budget constraints (Agran et al, 2017; Kleinert, Miracle, & Sheppard-Jones, 2007a; Pence & Dymond, 2016; U.S. GAO, 2010).…”
mentioning
confidence: 99%
“…Access to extracurricular activities is furthermore supported by the Americans with Disabilities Act (ADA, 1990), which requires state and locally funded programs to provide accommodations that enable individuals with disabilities to access services. Existing legislation and policy clearly support the inclusion of students with disabilities in school-sponsored extracurricular activities; yet, concerns continue about low levels of participation by students with disabilities (Pence & Dymond, 2016; U.S. GAO, 2010).…”
mentioning
confidence: 99%